Penerapan Model Konsep Teori Keperawatan Katherine Kolcaba - Suwalgiyah; Irna Nursanti (Sabda Abadi Nusantara, 2025)
Kolcaba’s Comfort Theory emphasizes the fulfillment of patient comfort through relief, ease, and transcendence across physical, psychospiritual, sociocultural, and environmental dimensions. This framework is highly relevant for fracture patients who often experience pain, anxiety, and sleep problems. This case study describes the application of Comfort Theory in nursing assessment, intervention, and evaluation for a 65-year-old woman (Mrs. G) with a closed distal radius fracture who underwent ORIF. Assessment was guided by Kolcaba’s comfort taxonomy, and nursing diagnoses were determined using the Indonesian Nursing Diagnosis Standards (SDKI). Interventions were structured into standard comfort measures, coaching, and comfort food for the soul, with outcomes evaluated using pain scores, behavioral observations, and subjective reports. The interventions resulted in a reduction of pain from 5 to 2, decreased anxiety reflected in more relaxed behavior and stable vital signs, and improved sleep quality with about five hours of uninterrupted rest. The patient also showed better participation in light ROM exercises and demonstrated more adaptive coping and optimism. Overall, increases in relief, ease, and transcendence were achieved. In conclusion, applying Kolcaba’s Comfort Theory effectively enhanced multidimensional comfort in a patient with a distal radius fracture. Strengthening nurse competencies, improving the care environment, and institutional support are recommended to optimize comfort-based nursing care.